Poverty Reduction Support Credits : Benin Country Study - Horton, Brendan (Washington, DC: World Bank, 2017)
Benin experienced a long period of political instability and economic challenges after achieving its independence in August 1960. In 1991 a new government initiated far-reaching reforms aimed at the creation of a market-based economy, resulting in significant liberalization of Benin's political and economic system. Growth fluctuated in the range of 4-6 percent until 2000, after which it began to trend downwards, fluctuating largely in response to variation in the exchange rate as well as to movement in the prices of cotton, Benin's main export, and oil, a major import. Benin benefited from support under the Environmental and Social Assessment Framework (ESAF) and Poverty Reduction and Growth (PRGF) facilities, the latter continuously since 1993. According to an independent ex-post review (International Monetary Fund 2004), program implementation during 1993-2003 was broadly successful. Real economic growth averaged 5 percent and fiscal consolidation improved as key initial challenges arising from the Government's low revenue collection and high wage bill were addressed. But overall progress in structural reform was mixed. Initial efforts to liberalize the economy and reduce government intervention were successful, and there was progress in introducing far-reaching reforms in the cotton sector. A new poverty reduction growth facility was approved in August 2005.